Benchmarking labour market performance and labour market policies: theoretical foundations and applications - Schütz, Holger,Speckesser, Stefan,Schmid, Günther (online, 1998)
Abstract:
urn:nbn:de:0168-ssoar-128821
Keywords: (stw)Arbeitsmarktpolitik; (stw)Wirkungsanalyse; (stw)Vergleich; (stw)Theorie; (stw)EU-Staaten; (thesoz)Hierarchie; (thesoz)Leistung; (thesoz)Betriebswirtschaftslehre; (thesoz)Benchmarking; (thesoz)Arbeitsmarkt; (thesoz)Management; (thesoz)Organisation; (thesoz)Arbeitsmarktpolitik; (thesoz)Indikator; (thesoz)Wettbewerb; (thesoz)Qualität; (thesoz)internationaler Vergleich; (thesoz)Beschäftigungssystem; Arbeitspapier; Graue Literatur; Buch; Arbeitsmarktpolitik; Beschäftigungspolitik; Wirkungsanalyse; Vergleich; Theorie